An Observational Study of Cerebral Blood Flow Velocity During Hypotensive Epidural Anesthesia. (January 2016) - Bombardieri, Anna Maria; Sharrock, Nigel E.; Ma, Yan; Go, George; Drummond, John C.
Abstract : BACKGROUND: Hypotensive epidural anesthesia (HEA), as practiced at our institution, uses sympathetic blockade to achieve mean arterial blood pressure (MAP) of ⩽50 mm Hg while administering epinephrine by infusion to support the circulation. HEA has not been associated with gross adverse effects on neurologic outcome or cognitive function in the postoperative period, suggesting adequate cerebral blood flow (CBF). However, the use of MAPs well below the commonly accepted lower limit of CBF autoregulation suggests that CBF should be significantly reduced below normal levels. To examine these conflicting hypotheses, we performed a prospective investigation of the effects of HEA on CBF velocity (CBFV), an accepted index of cerebral perfusion. METHODS: Fifty-two hip replacement patients were studied. HEA was induced by lumbar epidural injection of local anesthetic and infusion of epinephrine to achieve an MAP of ⩽50 mm Hg. Propofol/midazolam sedation was administered. Baseline CBFV was recorded pre-HEA (after sedation and before local anesthetic injection) and continuously thereafter. RESULTS: During HEA, MAP decreased by 40% and was stable throughout. The CBFVmean at baseline and at 3 HEA intervals during surgery was 46 ± 12 (SD), 45 ± 12, 47 ± 14, and 47 ± 14 cm·s −1, respectively. Although mean CBFVmean did not vary, there was considerable heterogeneity among patients. Twelve patients (23%) experienced reductions of CBFVmean of >20% during HEA intervals (99% lower confidence limit: 9%) and 6 (12%) reductions of >30% (99% lower confidence limit: 1%). There was no correlation between CBFVmean and MAP for MAPs between 100 and 40 mm Hg ( R 2 = 0.0015, P = 0.44). There were no instances of gross postoperative neurologic injury. CONCLUSIONS: Both hypotheses proved partially correct. CBFV was sometimes well maintained during HEA, despite MAPs well below the commonly accepted lower limit of autoregulation. However, there was considerable interindividual heterogeneity with 23% of subjects having CBFV reductions >20% (99% lower confidence limit: 9%), with some reductions approaching the threshold for ischemic injury. The present data do not allow us to determine whether hypotension would be similarly tolerated in other circumstances. Abstract : Published ahead of print October 13, 2015